1993
DOI: 10.1016/0014-5793(93)80821-b
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of a putative homolog of proline/arginine‐rich antibacterial peptides from porcine bone marrow

Abstract: Screening of a porcine bone marrow cDNA library with a PCR‐derived probe from rabbit LPS‐binding protein CAP18 led to the discovery of two closely related clones. The longer, full‐length cDNA clone encodes a 228 amino acid residue protein similar to the family of antibacterial/LPS‐binding cationic peptides. In contrast to other hitherto discovered precursors of Pro/Arg‐rich peptides from this family, they have a novel, unique structure of the C‐terminal region of 100 amino acid residues with a repeating sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 25 publications
1
38
0
1
Order By: Relevance
“…Pungercar et al [30] recently obtained from porcine bone marrow and sequenced two cDNA clones, C12 and C6, that encoded virtually identical proline and arginine rich antimicrobial peptides at the C-terminus of a cathelin-containing prepropeptide. The translated sequence of clone C 12 included a 30 residue, N-terminal signal peptide followed by a 198 residue protein whose N-terminal region was 84% identical to porcine cathelin in primary sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Pungercar et al [30] recently obtained from porcine bone marrow and sequenced two cDNA clones, C12 and C6, that encoded virtually identical proline and arginine rich antimicrobial peptides at the C-terminus of a cathelin-containing prepropeptide. The translated sequence of clone C 12 included a 30 residue, N-terminal signal peptide followed by a 198 residue protein whose N-terminal region was 84% identical to porcine cathelin in primary sequence.…”
Section: Discussionmentioning
confidence: 99%
“…If the prosequence were cleaved after the valine, which is the common cleavage site, as in the case of cathelin and several other cathelicidins [90], prophenin precursors would be processed into a 97-residue mature peptide. However, the actual mature products are prophenins-1 and -2, which contain only the C-terminal 79 residues.…”
Section: Prophenins Prolinephenylalanine-rich Amps With Repeated Decmentioning
confidence: 99%
“…In some cases, both peptide isolation and cDNA cloning have been accomplished. For example, Pungercar et al obtained two cDNA clones from porcine bone marrow, 'clone-12' and 'clone-6', that encoded nearly identical proline-rich antimicrobial peptides [18,19] and we independently purified the corresponding mature peptides, Prophenin (PF)-I and 2, from porcine leukocytes [17]. *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Recent cDNA cloning studies have revealed that many structurally and functionally diverse leukocyte antimicrobial peptides share a highly conserved pro-region, known as the 'cathelin' domain. Among these are bovine indolicidin, cyclic dodecapeptide, Bac 5 and Bac 7 [2 7]; rabbit 'P15' and CAP 18 [8][9][10][11]; porcine PR-39 [12,13], protegrins [14][15][16], prophenins [17][18][19], PMAP-23, PMAP-36 and PMAP-37 [20][21][22]; and human FALL-39/CAP-18 [23,24].…”
Section: Introductionmentioning
confidence: 99%